Concomitant autoimmunity and late cancers in adult-onset immunodeficiency due to neutralizing anti-IFN-γ autoantibodies - Tsai, Wan-Ting; Cheng, Chih-Yun; Sun, Hsin-Yun; Guo, Bei-Chia; Chiang, Ying-Chieh; Cheng, Chiao-Feng; Pan, Yi-Hua; Wu, Un-In; Wang, Jann-Tay; Sheng, Wang-Huei; Cheng, Aristine; Chen, Yee-Chun; et al. (Frontiers in Immunology, 2025)
BackgroundOpportunistic intramacrophagic infections are well-characterized in adult-onset immunodeficiency associated with neutralizing anti-IFN-γ autoantibodies (nAIGA).ObjectiveConcomitant autoimmune and neoplastic diseases are rarely described.MethodsThis study included 50 patients diagnosed with adult-onset immunodeficiency due to nAIGA between 2014-2024. Thirty-three were retrospectively included before January 2022, and 17 out of 295 screened patients were enrolled prospectively since January 2022. Ten patients were excluded due to missing records. All patients had regular follow-ups; anti-IFN-γ titers, autoimmune markers and cancer survey were conducted according to the primary physician’s evaluation.ResultsThe median age at diagnosis of adult-onset immunodeficiency was 57 years, and 53% were men. Malignancy occurred in 25%; genitourinary cancer predominated (n=4). Most (93%) patients had at least one positive autoimmune marker. Fifty-eight percent of patients were diagnosed with concomitant autoimmune diseases, and women (65%) predominated. Anti-nuclear antibody was positive in 61%, lupus anticoagulant in 50%, whilst autoimmune thyroiditis markers in 43%. Twenty-two percent of patients required long-term immunomodulation including biologic agents such as rituximab and daratumumab. Three patients (8%) died after a median interval of 9.4 years due to sepsis (n=2) and aggressive urothelial cancer (n=1). Most patients had decreasing nAIGA titers over time; two outliers with persistently high neutralizing antibodies developed late-onset malignancies.ConclusionAdult-onset immunodeficiency due to nAIGA is a syndrome associated with concomitant autoimmunity. Chronic infection and autoimmune-mediated inflammation may foster neoplastic changes, but the underlying mechanism is still undetermined. Autoimmune disease and cancer surveillance for patients with nAIGA is advised.